Strategy of post-neoadjuvant treatment of patients with residual breast cancer - V. V. Semiglazov; A. A. Natopkin (Опухоли женской репродуктивной системы, 2020)
The article considers the aspects of selection of post-neoadjuvant therapy for patients with residual breast cancer depending on biological subtype and molecular profile of the tumor. Analysis of morphological and molecular markers allowing to evaluate sensitivity of malignant breast tumors with high recurrence risk to new types of systemic treatment is presented.